2015
DOI: 10.1007/s00198-015-3214-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients do not have a consistent understanding of high risk for future fracture: a qualitative study of patients from a post-fracture secondary prevention program

Abstract: Our results suggest that health care providers' messages about fracture risk are confusing to patients and that these messages need to be modified to better suit patients' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…In addition, we found that the absolute fracture risk, expressed as a percentage, was often difficult to interpret for the patient as well as for the GP, and some patients felt the percentage was not high enough to start bisphosphonate treatment. The finding that patients have difficulties interpreting fracture risk was also found in another study [ 26 ]. Furthermore, a low risk perception was expressed by several patients as well as by GPs in our study and this might be partly caused by limited information on osteoporosis discussed during the medical consultation.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, we found that the absolute fracture risk, expressed as a percentage, was often difficult to interpret for the patient as well as for the GP, and some patients felt the percentage was not high enough to start bisphosphonate treatment. The finding that patients have difficulties interpreting fracture risk was also found in another study [ 26 ]. Furthermore, a low risk perception was expressed by several patients as well as by GPs in our study and this might be partly caused by limited information on osteoporosis discussed during the medical consultation.…”
Section: Discussionsupporting
confidence: 65%
“…Investigating the causal pathways by which osteoporotic fractures may lead to preventable mortality is not simply an intellectually interesting exercise. Recent studies have documented persistent undertreatment of those with osteoporosis and recent osteoporotic fractures, declining use of pharmacologic fracture prevention therapies and underappreciation by patients as to why a recent fracture signals that they are at high risk for subsequent fractures and other adverse events . It is important that we establish, as best as we can, the extent and mechanisms by which prevention of fractures may delay mortality.…”
Section: What Proportion Of Post‐fracture Mortality Is Caused By the mentioning
confidence: 99%
“…Recent studies have documented persistent undertreatment of those with osteoporosis and recent osteoporotic fractures, (76,77) declining use of pharmacologic fracture prevention therapies (78) and underappreciation by patients as to why a recent fracture signals that they are at high risk for subsequent fractures and other adverse events. (79) It is important that we establish, as best as we can, the extent and mechanisms by which prevention of fractures may delay mortality. This will facilitate communicating cogent, convincing explanations ("connecting the dots") to patients at high risk of fracture, their health care providers, health care delivery organizations, and health care payers regarding the short-and long-term adverse effects (including mortality) of fractures and why their prevention is important.…”
Section: What Proportion Of Post-fracture Mortality Is Caused By the mentioning
confidence: 99%
“…Accurate perception of risk is crucial for the rational adoption of treatment. Communicating risk and benefit of pharmacological treatment to patients remains a great challenge [23]. Many tools and strategies [24], developed by investigators (such as the Mayo Clinic Osteoporosis Choice decision aid https://osteoporosisdecisionaid.mayoclinic.org/index.php/ site/index) and patient societies, aim to support decisionmaking; however, in our experience and as has been highlighted in recent publications [25], healthcare providers' messages about fracture risk are confusing to patients and much work is still required so that communications better suit patients' needs.…”
Section: Discussionmentioning
confidence: 99%